John Paul II about the logic of the dialogue between the Catholic Church and Islam - Prysukhin, Sergiy (Ukrai͏̈ns'ke relihijeznavstvo, 2015)
The article of Sergiy Prysukhin «John Paul II about the logic of the dialogue between the Catholic Church and Islam» is devoted to philosophical and theological developments of Pope John Paul II in relation to the analysis of substantial characteristics of the concept «dialogue between Catholicism and Islam», and the logic of its implementation in a complex and contradictory present.